Google Sites-Based Teacher Administration in Elementary Schools - Deka Susnita; Riswan Jaenudin; Syarifuddin; Makmum Raharjo (Jurnal Edutech Undiksha, 2024)
There are still many teachers who have difficulty planning learning activities carefully. The majority of teachers do not complete the administration book because it has to be done manually. Therefore, this research aims to develop Google Sites-based teacher administration in elementary schools. This type of research is development research using the Rowntree model to produce and test products. Meanwhile, at the material evaluation stage, tessmer formative evaluation is used. This research involved material experts, language experts, design experts and practitioner experts. The subjects of this research were class and study teachers in elementary schools with a total of 21 people. Data collection was carried out by observation, interviews, documentation and tests. The instrument used to collect data was a questionnaire sheet. Data were analyzed using qualitative, quantitative and N-gain descriptive analysis. The results of the practicality test at the one to one test stage obtained an average of 90.83% and the small group test obtained an average of 92.75% (very practical). The results of the effectiveness test on the pretest and posttest results with an average N-gain value of 0.74, high category. It can be concluded that teacher administration with Google Sites innovation in elementary schools is very valid and practical for teachers to use. This research has implications for the development of Google Sites-based teacher administration which in the future can improve teacher performance.